A SNARE-like protein from Solanum lycopersicum increases salt tolerance by modulating vesicular trafficking in tomato - Salinas-Cornejo, Josselyn; Madrid-Espinoza, José; Verdugo, Isabel; Norambuena, Lorena; Ruiz-Lara, Simón (Frontiers in Plant Science, 2023)
Intracellular vesicular trafficking ensures the exchange of lipids and proteins between endomembrane compartments. This is relevant under high salinity conditions, since both the removal of transporters and ion channels from the plasma membrane and the compartmentalization of toxic ions require the formation of vesicles, which can be maintained as multivesicular bodies or be fused to the central vacuole. SNARE proteins (Soluble N-ethylmaleimide-sensitive factor attachment receptor) participate in the vesicle fusion process and give specificity to their destination. Plant genome studies have revealed a superfamily of genes that encode for proteins called SNARE-like. These proteins appear to be participating in vesicular trafficking with similar functions to those of SNARE proteins. A SNARElike, named SlSLSP6, in Solanum lycopersicum plants has been shown to be induced under high salinity conditions. A phylogenetic relationship of SlSLSP6 with SNARE-like proteins of salinitytolerant plants, including Salicornia brachiata, Zostera marina and Solanum pennelli, was determined. Considering its amino acid sequence, a putative clathrin adapter complex domain and palmitoylation site was predicted. Subcellular localization analysis evidenced that SlSLSP6 is mostly localized in the plasma membrane. Using transgenic tomato plants, we identified that overexpression of SlSLSP6 increased tolerance to salt stress. This tolerance was evident when we quantified an improvement in physiological and biochemical parameters, such as higher chlorophyll content, performance index, efficiency of photosystem II and relative water content, and lower malondialdehyde content, compared to control plants. At the subcellular level, the overexpression of SlSLSP6 reduced the presence of H2O2 in roots and increased the compartmentalization of sodium in vacuoles during salt stress. These effects appear to be associated with the higher endocytic rate of FM4-64, determined in the plant root cells. Taken together, these results indicate that SlSLSP6 increases tolerance to salt stress by modulating vesicular trafficking through over-induction of the endocytic pathway. This work contributes to understanding the role of this type of SNARE-like protein during salt stress and could be a potential candidate in breeding programs for tolerance to salt stress in tomato plants.